2015
DOI: 10.1103/physreva.92.053621
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional discrete compactons in nonlinear Schrödinger lattices with strong nonlinearity management

Abstract: The existence of multidimensional lattice compactons in the discrete nonlinear Schrödinger equation in the presence of fast periodic time modulations of the nonlinearity is demonstrated. By averaging over the period of the fast modulations, an effective averaged dynamical equation arises with coupling constants involving Bessel functions of the first and zeroth kinds. We show that these terms allow one to solve, at this averaged level, for exact discrete compacton solution configurations in the corresponding s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In particular, the existence of one-dimensional compactons in BEC arrays [5] and in binary BEC mixtures with time modulated intra-spices scattering length [6], as well as, the existence of compactons and vortexcompactons (e.g. vortices on a compact support) in two-dimensional DNLSE [7], were recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the existence of one-dimensional compactons in BEC arrays [5] and in binary BEC mixtures with time modulated intra-spices scattering length [6], as well as, the existence of compactons and vortexcompactons (e.g. vortices on a compact support) in two-dimensional DNLSE [7], were recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view appears particularly interesting the theoretical work done on compactons of the discrete nonlinear Schrödinger equation (DNLSE), a model that is linked to physical systems such as nonlinear optical waveguides arrays and Bose-Einstein condensates (BEC) trapped in deep optical lattices (OL). In these contexts, it has been demonstrated that when subjected to periodic time dependent rapid modulations of the nonlinearity, also called strong nonlinearity management (SNM) limit, the DNLSE can support stable compactons of different types [5,6,7]. In particular, the existence of one-dimensional compactons in BEC arrays [5] and in binary BEC mixtures with time modulated intra-spices scattering length [6], as well as, the existence of compactons and vortexcompactons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4.6.1). More recently it was shown that compactons also can exist in a DNLS model with a fast, periodic modulation of the nonlinearity, both in one- [35] and several-dimensional [36] lattices. By time averaging over the fast modulation, the (nearest-neighbor) coupling becomes density dependent, and it will also vanish for certain amplitudes which allow for compactons.…”
Section: Lattice Compactonsmentioning
confidence: 99%
“…Note that this is the experimental scheme discussed in Refs. [35,36], however within a DNLS context, for realizing lattice compactons (see Sec. 1.3.4).…”
Section: Extended Bose-hubbard Modelsmentioning
confidence: 99%
See 1 more Smart Citation